Digital-Based Database Governance Development Management with Master Data Management UIN K.H. Abdurrahman Wahid Pekalongan - Nurlaila Ana (Universitas PGRI Semarang, 2023)
Academic and Student Service Management (AKMA) expects that there will be an information system data management that can be accessed by all parties. The research aims to analyze the influence of database governance development management and digitization on master data management. The research design is a positivistic quantitative descriptive approach with multiple regression analysis. The research population is all Lecturers, Students, AKMA Sections, UTIPD Sections, and LPPM. The sampling technique is the percentage of cluster random sampling. Research results the effect of database governance on master data management is 93%, and the effect is positive and significant. The effect of digitalization on master data management is 52.8%, the effect is positive and significant. The regression equation Y=0.930X1+0.528X2 with R2=0.875. Suggestion: AKMA can properly apply a digital-based database governance development management system with master data management.